Pengaruh Budaya Organisasi Terhadap Motivasi Karyawan PT Telekomunikasi Indonesia, Tbk Area Wilayah Sidoarjo - Rizka Novianty Haninda; Rekza Yan Hermawan (Fakultas Ekonomi Universitas Yos Soedarso, 2022)
The purpose of this study was to determine the effect of organizational culture on the motivation of employees of PT Telekomunikasi Indonesia, Tbk in Sidoarjo. The method in this research is descriptive method. The population in this study were all employees of PT Telkom Telekomunikasi Indonesia, Tbk in Sidoarjo, with a sample of 95 employees. The simple linear regression equation obtained is, namely: Ŷ = 3.678 + 0.102 X, a positive coefficient means that there is a positive relationship between organizational culture and employee motivation. If organizational culture increases employee motivation will also increase. While the strength of the relationship between organizational culture and employee motivation with a coefficient (R) of 0.102, which means the relationship between organizational culture and employee motivation at PT Telekomunikasi Indonesia, Tbk, Sidoarjo Region can be said to show a very weak relationship. And for the determination coefficient R ^ 2, organizational culture in influencing employee motivation has a value of 1% and the remaining 99% is influenced by other variables outside this study. By using the feasibility test model F calculate <F table (0.982 <3.94) so that Ha is rejected and the probability value (sig) is 0.324> 0.05. It means that a simple linear regression model cannot be used to predict employee motivation which is influenced by organizational culture.